(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2023)
The fisheries sector has a role in food security, sovereignty, and self-sufficiency. Fish as an animal food has the potential for nutritional content that can reduce nutritional problems. North Sumatra has abundant fishing resources. The aim of this research is to forecast the amount of fish production by fulfilling animal protein needs in the population in North Sumatra. The method used is a descriptive quantitative and time series approach using secondary data analysis (ADS). The research was conducted in April–May 2023. The population used in the study was all time series data on fish production, both marine and inland, in North Sumatra for 2010–2022, and data on Indonesia’s population for 2010–2022. The projected results of fishery production in 2022–2025 look to be fluctuating but tend to increase. The projected average fishery production is 585.761 tons. The average protein sourced from fish production in North Sumatra still fulfills 31% of the daily protein adequacy rate. Population projections that continue to increase show that the availability of fish has not fulfilled the daily consumption of the people of North Sumatra.